The high-resolution crystal structure of phosphatidylinositol 4-kinase IIβ and the crystal structure of phosphatidylinositol 4-kinase IIα containing a nucleoside analogue provide a structural basis for isoform-specific inhibitor design - Klima, Martin; Baumlova, Adriana; Chalupska, Dominika; Hřebabecký, Hubert; Dejmek, Milan; Nencka, Radim; Boura, Evzen (Acta crystallographica. Section D, Biological crystallography, 2015)
Phosphatidylinositol 4-phosphate (PI4P) is the most abundant monophosphoinositide in eukaryotic cells. Humans have four phosphatidylinositol 4-kinases (PI4Ks) that synthesize PI4P, among which are PI4K IIβ and PI4K IIα. In this study, two crystal structures are presented: the structure of human PI4K IIβ and the structure of PI4K IIα containing a nucleoside analogue. The former, a complex with ATP, is the first high-resolution (1.9 Å) structure of a PI4K. These structures reveal new details such as high conformational heterogeneity of the lateral hydrophobic pocket of the C-lobe and together provide a structural basis for isoform-specific inhibitor design.
Keywords: Catalytic Domain; adenosintrifosfát; ATP; Humans; inhibitory proteinkinas; Nucleosides; Hydrophobic and Hydrophilic Interactions; nukleosidy; Protein Conformation; krystalografie rentgenová; inhibitor; Crystallography, X-Ray; lidé; phosphatidyl inositol; Drug Design; protein - isoformy; Protein Isoforms; Protein Kinase Inhibitors; Adenosine Triphosphate; 1-Phosphatidylinositol 4-Kinase; 1-fosfatidylinositol-4-kinasa; katalytická doména; racionální návrh léčiv; kinase; crystal structure; hydrofobní a hydrofilní interakce; konformace proteinů